Nabi Yusuf AS dan Makna Pendidikan dalam Islam - Kalam Setia; Hafizian Nur; Zawawi Ismail (Fikiran Masyarakat, 2014)
Al-Qur'an is the holy book of Allah Almighty revealed to the Prophet Muhammad and therein lies the story of the previous ummah. Among of story contained in the Qur’an is prophet Yusuf AS life story. It is began from dreaming and separated from his father until he was reunited with his family in Egypt, thrown into the well and at the end, he was experienced the happiness of his life; he met with his family who have been separated and assembled in one country is Egypt. This story is more emphasis on the life difficulties of prophet Yusuf AS at the young age. This paper discusses the philosophy of education in the story of the Prophet Yusuf AS. Education with the methods of the story of stories, particularly stories of the Qur'an has benefit in the human psyche because among the characterisitics of the story of the Qur'an can be evocative of the soul and increase faith to Allah Almighty. Aspects of educational philosophy in the story of Prophet Yusuf AS in Surat Yusuf verses 23-29 are three statements of Yusuf AS to avoid fornication, first: seek refuge in Allah SWT, second: remember the kindness and the third one: remember the effect of the sin actions, it would not be lucky people who do wrong. Philosophy of education is muraqabah (always being watched Allah SWT), genuine sincerity, honest, discreet, often istighfar, and repent to Allah Subhanahu Wa Ta’ala.